2022
DOI: 10.1158/1535-7163.mct-21-0599
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anti-LY6G6D/CD3 T-Cell–Dependent Bispecific Antibody for the Treatment of Colorectal Cancer

Abstract: New therapeutics and combination regimens have led to marked clinical improvements for the treatment of a subset of colorectal cancer (CRC). Immune checkpoint inhibitors have shown clinical efficacy in patients with mismatch repair-deficient or microsatellite instability-high (MSI-H) metastatic CRC (mCRC). However, patients with microsatellite-stable (MSS) or low levels of microsatellite instable (MSI-L) CRC have not benefited from these immune modulators, and the survival outcome remains poor for the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…In this study, we describe the identification of LY6G6D as a high tumor specific antigen in CRC, specifically in MSS tumors, confirming the same observations made by other groups ( 7 , 23 ). This is an important finding since MSS is the most abundant CRC subtype and presents a poor response rate to immuno-oncology treatments ( 24 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we describe the identification of LY6G6D as a high tumor specific antigen in CRC, specifically in MSS tumors, confirming the same observations made by other groups ( 7 , 23 ). This is an important finding since MSS is the most abundant CRC subtype and presents a poor response rate to immuno-oncology treatments ( 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…This is an important finding since MSS is the most abundant CRC subtype and presents a poor response rate to immuno-oncology treatments (24). As confirmed by immunohistochemistry analysis by Wang et al in a recent publication (23), the expression distribution of LY6G6D makes this target a rare tumor specific antigen with differential expression in CRC versus normal tissues, which allows the generation of a TcE with very restricted on-target/ off-tumor toxicity. To further demonstrate the relevance of LY6G6D, we performed a prevalence analysis in CRC samples by immunohistochemistry and confirmed that 27% of the samples express LY6G6D on tumor cells.…”
Section: Discussionmentioning
confidence: 88%
“…Some of the marker genes of these clusters were associated with tumor progression, such as LYPD3 and LY6G6D. LY6G6D up-regulation was predominant in MSS CRCs characterized by an enrichment of immune suppressive regulatory T-cells and a limited repertoire of PD-1/PD-L1 immune checkpoint receptors ( 30 , 31 ). Thus, LY6G6D has been used as a target for CRC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro functional assays showed that LY6G6D-TDB-mediated T-cell activation and cytotoxicity are conditional and target-dependent (Wang et al, 2022) (Figure 4). In mouse xenograft tumor models, enhanced efficacy can be achieved when LY6G6D-TDB is combined with PD-1 blockade (Wang et al, 2022). The LY6G6D/CD3 TcE developed by (Corrales et al, 2022) similarly exhibits targeted killing of target-positive cells in in vitro experiments where LY6G6D expression is homogeneous among cells.…”
Section: Targeting Ly6g6d To Unlock Anti-tumor Immunity In Pmmr Crcmentioning
confidence: 99%
“…Zhang, Z., Huang, L., Li, J.,& Wang, P. (2022). Bioinformatics analysis reveals immune prognostic markers for overall survival of colorectal cancer patients: a novel machine learning survival predictive system.…”
mentioning
confidence: 99%